2014
DOI: 10.1093/trstmh/tru163
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of serological assays for viral hemorrhagic fevers and determination of the prevalence of Rift Valley fever in Borno State, Nigeria

Abstract: The seroprevalence of RVF was significantly higher than that of LASV and CCHF in Borno State, Nigeria. The RVFVpv-based neutralization assay developed in this study has the potential to replace the traditional assays based on live viruses for the diagnosis and seroepidemiological studies of RVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…A previous study in Borno State using 297 samples collected from patients attending health facilities between September 2011 and February 2012 showed a prevalence rate for IgG antibodies against CCHFV of 2.4% using a similar ELISA test to that used in this study [34]. The difference in IgG levels may be due to different study populations, for example our report was conducted on samples collected from 4 LGAs whereas the earlier report was conducted on samples from 10 LGAs [34]. In 1974, it was reported that 9.6% of 250 sera collected in Nigeria had neutralisation activity specific to CCHFV [35].…”
Section: Discussionmentioning
confidence: 72%
“…A previous study in Borno State using 297 samples collected from patients attending health facilities between September 2011 and February 2012 showed a prevalence rate for IgG antibodies against CCHFV of 2.4% using a similar ELISA test to that used in this study [34]. The difference in IgG levels may be due to different study populations, for example our report was conducted on samples collected from 4 LGAs whereas the earlier report was conducted on samples from 10 LGAs [34]. In 1974, it was reported that 9.6% of 250 sera collected in Nigeria had neutralisation activity specific to CCHFV [35].…”
Section: Discussionmentioning
confidence: 72%
“…Pseudotype viruses bearing the G protein of VSV (VSVpv), GP of RVFV (RVFVpv), and murine leukemia virus (MLV) envelope protein (MLVpv) were generated as described previously (17,18). In brief, HEK 293T cells were grown to 70% confluence on collagen-coated tissue culture plates and then transfected with each of the expression vectors pKS-SFTSV-GP, pKS-RVFV-GP, pCAG-VSV-G, and pFBASALF (which expresses MLV envelope proteins; provided by T. Miyazawa, Kyoto University).…”
Section: Methodsmentioning
confidence: 99%
“…A major advantage of using MERSpv for neutralization assays is that infection can be detected earlier when using a VSV backbone than when using a lentivirus backbone. Furthermore, VSV pseudotypes can be applied for highthroughput screening for neutralizing antibodies [4]. MERSpv-St16 may be a useful reagent that can provide a…”
Section: Discussionmentioning
confidence: 99%